PERBEDAAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI MENGGUNAKAN METODE PROBLEM SOLVING DENGAN METODE CERAMAH DISKUSI DI SMA MUHAMMADIYAH 2 PALEMBANG - Karyadi Hidayat (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
Learning method is a step that is done so that certain goals in the learning process can be achieved. There are many learning methods, such as problem solving method and discussion discourse method. This research is conducted with the aim to know the more appropriate method used in studying economics. There are two independent variables in this study, with symbols of variables X1 and X2. The method used is experimental and comparative descriptive. Technique of data analysis using t test equation with 95% confidence level (α 0,05). This study shows that the problem solving method is more appropriate to be used in economic learning, because the learning result obtained by students using this method is higher than the lecture discussion method. Likewise with the average difference test results performed show that there is a significant difference between the two.